KARAKTERISTIK DEWAN DIREKSI DAN ESG: PERAN MODERATING UKURAN PERUSAHAAN - Ina Nusuki; Wahdan Arum Inawati; Fanji Farman; Novy Fajrianti (JURNAL ILMIAH EDUNOMIKA, 2026)
This study investigates how corporate governance affects ESG (Environmental, Social, and Governance) aspects in Indonesia from 2020 to 2024. Using panel data regression and Commission Size, Audit Size, and Independent Commissioners, as well as their collective impact on ESG (Environmental, Social, and Governance) is measured using ESG scores, risk ratings (such as Sustainalytics), or sustainability indices (such as the IDX ESG Index). These measurements assess environmental (emissions, waste), social (employees, community), and governance (ethics, shareholder rights) impacts to determine a company's sustainability and risk. Based on agency theory, legitimacy, the findings show that Board Size, Audit Size, and Independent Directors significantly improve ESG, supporting the idea that they can enhance sustainability oversight. Conversely, board size and meeting frequency do not show consistent effects, challenging conventional assumptions in agency and stakeholder theories. It should be noted that board independence has a negative impact on ESG, highlighting the challenges of contextual governance in Indonesia. Independent Commissioners emerge as a stronger predictor of ESG than individual attributes, confirming that integrated governance mechanisms better explain corporate transparency.